The Newspeak of the Polish People’s Republic in the Mirror of the Comments by Michał Głowiński - Plęs, Łukasz M. (Hassrede – ein multidimensionales Phänomen im interdisziplinären Vergleich, 2020)
This article deals with the issue of the newspeak as it was used in the Polish People’s Republic, with special regard to the remarks by Michał Głowiński. The comments were created from the mid-sixties to the decline of the Polish People’s Republic and based on the reading of the daily “Trybuna Ludu” (“People’s Tribune”). Głowiński provides an in-depth analysis and levels harsh criticism at the propaganda language of the state authorities, revealing the mechanisms of manipulation. The notes were officially published in a few volumes not until the nineties, however they are unique due to the fact that they came into being systematically at the time the newspeak of the Polish People’s Republic was used.